Zastrupitve s kemičnimi bojnimi strupi - Sollner Dolenc, Marija (Medicinski razgledi, 2011)
Chemical warfare agents are defined as any chemical substance whose toxic properties are utilized to kill, injure or incapacitate an enemy in warfare and associated military operations. There has been a legislative effort worldwide to ban the use of them under the chemical weapons convention which came into force in 1997. However the manufacture of these agents cannot be completely prohibited as some of them have potential industrial uses. The easeof manufacturing these agents and effectiveness during combat or small-scale terrorist operations still make them a powerful weapon to reckon with. In this review we will discuss briefly about properties, mechanism of toxicity, clinical features of exposure and pharmacological management of poisoning caused by chemical agents.
Keywords: kemično orožje; zastrupitve; živčni strupi